(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The article focuses on the relevance and effectiveness of the use of modern digital educational technologies in teaching process. Various digital tools are being considered that can be used not only for teaching, but also for assessment, including LMS platforms for testing, document management, gamification, virtual labs, interactive whiteboards and digital laptops.